أسس تصميم الإضاءة النهارية للمكاتب - بدوان غسان; شحود رؤى (Latakia University Journal -Engineering Sciences Series, 2019)
يعدّ بعض المعماريين تصميم الإضاءة النهارية في المكاتب على أنه قضية فهمٍ وخبرةٍ بشكلٍ عامٍ ويأتي كنتيجة لتصميم الواجهات والفتحات إذ يتم تعويض نقص الإضاءة النهارية باستخدام الإضاءة الاصطناعية كحل آمن ومكمل، ومع الاهتمام والوعي بتوفير الطاقة وحماية البيئة وإدراك أهمية الراحة البصرية وانعكاسها على مردود العاملين، أصبح تصميم الإضاءة النهارية أكثر أهمية وعلمية ومهنية .لأنها تؤثر العديد من الاعتبارات التصميمية للضوء على المبنى من ناحية الشكل والمظهر. وربما المحدد التصميمي الأكثر أهميةً عند تطبيق استراتيجيات الإضاءة النهارية يعتبر هندسة جدران المبنى والسقف والأرضيات والنوافذ والعلاقة فيما بينها، وهي مهمة لفهم العلاقات الهندسية وفقاً لوظائف الإضاءة، بالإضافة إلى فهم العلاقات الكمّية التي ترافق الأشكال الهندسية المتنوعة. يتوجب على المصممين التعامل مع الإعدادات وقياس النتائج قبل أن يفهموا بشكلٍ ملائم العلاقات الكمية. يمكن تحقيق هذا عبر اختبارات النموذج، محاكاة الحاسب، أو كليهما. وسيتناول هذا البحث أهمية الإضاءة النهارية وتأثيرها في إنتاجية العاملين في أبنية المكاتب والأسس المعتمدة في تصميم الإضاءة النهارية لأبنية المكاتب. Some Architects consider the day lighting design in Offices is a matter of understanding and skill in general and is a consequence of designing the facades and openings, and the lack of natural lighting is supplemented by using artificial lighting as a safe and additional solution, putting in mind the issues of energy saving, environment protection, the importance of visual comfort and its effect on the workers’ productivity, day lighting design became more important, scientific and professional. Many lighting design aspects affect the shape and appearance of the building. The most important designing determiner in applying day lighting strategies is the geometry of walls, ceiling, floors, windows and the relation between them, and they are important to understand the geometric relations according to lighting functions, in addition to understanding the quantitative relations that accompany the various geometric shapes. The designers should deal with the arrangements and measure the results before they understand the quantitative relations. This can be achieved by model testing, computer simulation, or both of them. This research is going to study the importance of day lighting and its effect on workers’ productivity in offices’ buildings and the adopted principles in designing the day lighting of offices’ buildings.